Factors influencing impulsive buying in live streaming: A conceptual framework - Ho, Kai Hung; Yapp, Emily Hon Tshin; Sharinah Puasa (2022)
Due to the widespread COVID-19 pandemic, many physical stores are prohibited to function, resulting in the emergence as well as general use of online shopping. This study looks into the effect of perceived value of bundle offers and telepresence values on impulse buying in live streaming. An online survey will be conducted among Malaysian who view live streaming. The expected outcome of this study is that consumers' perceived value of bundle offer and telepresence will be positively correlated with online impulse buying. The first limitation in this study is focusing only on one social media platform with a live streaming function, Facebook. The second limitation could be that all the respondents in this study had experience in using live streaming in Facebook only. This research will benefit live streamer and e-retailer to further understanding consumes' buying behavior. Originality/value: This study identifies the relationship of the perceived value of bundle offers and telepresence with impulse buying in live streaming. Pervious study will either concentrate on the perceived value of bundle offers or telepresence. However, both perceived value of bundle offer and the telepresence will influence impulse buying. Due to that, it is essential to incorporate both the perceived value of bundle offer and telepresence when examine impulse buying in live streaming.